Analysis of immediate use of sunscreen after microneedling. Issue 6 (16th June 2021) - Meyer, Patrícia Froes; Silva, Rodrigo Marcel Valentim da; Carreiro, Eneida de Morais; Borges, Fábio dos Santos; Silva, Francy Richarles da Cruz; Vieira, Bruno Haysllan de Araújo; Maia, Rafaella Rêgo; Queiroga Farias, Stephany Luanna; Soares, Ciro Dantas; Rodrigues, Joyce; Pasqual, Gustavo Felipe
Abstract: Introduction: Microneedling promotes skin microlesions that lead to an inflammatory process, increasing cell proliferation, cell metabolism, and synthesis of collagen and elastin, therefore restoring skin integrity. Objective: This study aims to investigate the differences between the physical and the physical‐chemical sunscreen application after microneedling, assessed through histological analysis. Method: This was a two‐phase study. The first phase investigated the physical and physical‐chemical sunscreen penetration mixed with India ink through histological analysis. The sunscreens were applied after the microleakage in vivo on the skin of a volunteer who underwent abdominoplasty 24 hours after the procedure. Histological analyses were carried out using optical and electron microscopy. The second phase analysed the skin reactions with the use of physical sunscreen after different microneedling treatments. The sample consisted of 30 volunteers distributed into three groups: G1 received the "Roller" microneedling, G2 received pen micropuncture treatment, and G3 received the fractional radiofrequency treatment. Results: The histological analyses of the first phase indicated that the physical‐chemical protection sunscreen penetrated more deeply, and pigment was found among the collagen fibres and the dermal fibroblast cytoplasm in comparison to the physical protection sunscreen, which had the pigment confined exclusively in the superficial epidermis layer. The second phase results demonstrated that the use of the physical protection sunscreen after the different microneedling techniques showed no adverse reactions such as itching, pain or soreness, and the hyperaemia. Conclusion: The proposed intervention showed that the use of physical protection sunscreen after different microneedling procedures is safe.